Development of girl-students’ physical qualities at extracurricular cheer-dance classes (cheer-dance show) - D.V. Pyatnickaya (Physical Education of Students, 2015)
Purpose: to work out and substantiate methodic of cheer-dance means’ usage in extracurricular trainings of girl students. Material: in experiment 450 girl-students of 17-20 years’ age participated. Results: we generalized theoretical knowledge and practical experience in selection, content and organization of girl students’ physical education. We presented the data of comparative analysis of girl students’ physical condition and (sportswomen and not sportswomen). We noted significant interest to physical education, in which the offered methodic is used. It was found that demands in health strengthening can be formed by means of dance kinds of cheer-leading (cheer-dance and cheer-dance show). Conclusions: We have found prospects of girl students’ physical education perfection. It permits to work out different variants of realization of educational health related strategy.